Electrode Edge Cobalt Cation Migration in an Operating Fuel Cell: An In Situ Micro-X-ray Fluorescence Study. Issue 6 (14th March 2018) - Cai, Yun; Ziegelbauer, Joseph M.; Baker, Andrew M.; Gu, Wenbin; Kukreja, Ratandeep S.; Kongkanand, Anusorn; Mathias, Mark F.; Mukundan, Rangachary; Borup, Rod L.
Abstract : PtCo-alloy cathode electrocatalysts release Co cations under operation, and the presence of these cations in the membrane electrode assembly (MEA) can result in large performance losses. It is unlikely that these cations are static, but change positions depending on operating conditions. A thorough accounting of these Co cation positions and concentrations has been impossible to obtain owing to the inability to monitor these processes in operando. Indeed, the environment (water and ion content, potential, and temperature) within a fuel cell varies widely from inlet to outlet, from anode to cathode, and from active to inactive area. Synchrotron micro-X-ray fluorescence (μ-XRF) was leveraged to directly monitor Co 2+ transport in an operating H2 /air MEA for the first time. A Nafion membrane was exchanged to a known Co cation capacity, and standard Pt/C electrocatalysts were utilized for both electrodes. Co Kα1 XRF maps revealed through-plane transient Co transport responses driven by cell potential and current density. Because of the cell design and imaging geometry, the distributions were strongly impacted by the MEA edge configuration. These findings will drive future imaging cell designs to allow for quantitative mapping of cation through-plane distributions during operation.